Effects of slaughter knife sharpness on blood biochemical and electroencephalogram changes in cattle - Imlan, Jurhamid Columbres; Kaka, Ubedullah; Goh, Yong Meng; Idrus, Zulkifli; Mohamed, Elmutaz Atta Awad; Abubakar, Ahmed Abubakar; Ahmad, Tanbir; Hassan Nizam, Quaza Nizamuddin; Sazili, Awis Qurni (MDPI, 2020)
The sharpness of the knife used for slaughter is of the utmost importance from an animal welfare perspective. The quantification of knife sharpness is almost impossible in abattoirs. The sharpness of the knife blade used to slaughter an animal, as well as its effects on animals’ pain and stress levels, is an important area of investigation that needs to be addressed. The objective of this study was to evaluate the effects of knife sharpness on blood biochemical parameters, plasma catecholamines, and electroencephalographic (EEG) responses. Twenty Brahman crossbred steers were either subjected to slaughter with a sharp knife (n = 10) or a commercial sharp knife (n = 10); knife sharpness was measured with the ANAGO® sharpness tester. There was significant increase in adrenaline (p < 0.0001), glucose (p = 0.0167), creatinine kinase (p = 0.0123) and lactate dehydrogenase (p = 0.0151) at post-slaughter compared to pre-slaughter in commercial sharp knife group than in the sharp knife group. A significant increase was observed in the median frequency (p < 0.0001) and total power (p < 0.0001) of the EEG, the parameters for pain and stress, in the animals slaughtered with the commercial sharp knife than those slaughtered with the sharp knife. Thus, EEG results also supported the hormonal and biochemical results. From the results, it is concluded that animals slaughtered with a sharp knife experienced the least amount of pain and stress compared to those slaughtered with a commercial sharp knife.